One‐Pot Synthesis of Fused Indolin‐3‐Ones via a [3+3] Cycloaddition Reaction. Issue 22 (23rd September 2021) - Huang, Lang; Yao, Zhenyu; Huang, Guanghua; Ao, Yaqi; Zhu, Bin; Li, Sanshu; Cui, Xiuling
Abstract: A formal [3+3] cycloaddition reaction of azaoxyallyl cations and isatogens generated in situ from α ‐halo hydroxamates and o ‐nitroalkynes, respectively, was developed. The cycloisomerization of the o ‐nitroalkynes, followed by base‐mediated elimination of hydrogen halide and 1, 3‐dipolar cycloaddition of the azaoxyallyl cations with the isatogen intermediates, were hallmarks of this one‐pot tandem reaction. A series of tricyclic fused indolin‐3‐ones were obtained under very mild reaction conditions with high atom economy, and the reaction exhibited excellent functional group tolerance. In addition, the reaction was highly scalable to multigram quantities. The obtained indolin‐3‐ones exhibited robust DNA staining patterns in agarose gel electrophoresis. Coupled with the fluorescence properties of the products, these results highlight the potential utility of tricyclic fused indolin‐3‐ones in various fluorescence and cell‐staining applications. Abstract :